2013
DOI: 10.1080/03650340.2012.725938
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiological attributes under summer/winter crops rotation in a no-tillage system

Abstract: Knowledge of the effect of a multiple combination of summer/winter crop rotation on the microbiological properties of soil would allow a more adequate response to its use. This study aimed to evaluate the effect of the rotation of three summer crops (continuous soybean, continuous maize and soybean/maize rotation) in combination with seven winter crops (maize, sunflower, oilseed radish, millet, pigeon pea, sorghum and sunn hemp) on the microbiological properties of the soil. A soybean/maize (SM) rotation had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…These microorganisms are the main agents responsible for GHG production, being highly responsive to any change in the environment. Thus, processes that result in GHG emissions depend directly on the functional diversity and structure of soil microbial communities 82 , 83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These microorganisms are the main agents responsible for GHG production, being highly responsive to any change in the environment. Thus, processes that result in GHG emissions depend directly on the functional diversity and structure of soil microbial communities 82 , 83 .…”
Section: Resultsmentioning
confidence: 99%
“…Microorganism populations play an essential role in recycling soil chemical elements by controlling the dynamics of the decomposition and stabilization of carbon 85 and, consequently, spatiotemporal variability patterns of FCO 2 into the atmosphere. Moreover, the functional diversity and structure of soil microbial communities are of particular importance for soil functioning as an ecosystem 82 , 83 . In this sense, the pmo A gene has been widely used to detect the presence of methanotrophic bacteria in the soil because they have the ability to use methane as the sole source of carbon and energy and hence play an important role in the global carbon cycle, being potential biodegrading agents 86 .…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme activities in soil are important markers of soil fertility and are considered to be major factors contributing to overall soil quality and productivity [ 31 ]. Previous studies have shown that the extension of the fixed number of years of a crop leads to a reduction in the activity of some soil enzymes, and is an important barrier factor to productivity [ 32 ]. However, crop rotation increases soil enzyme activities by 10% to 86% compared with those of continuous cropping [ 33 ], similar to the effect of amending soils with organic manure [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biomass P also had a significant correlation with glutaminase at both soil layers, suggesting a strong interaction. The different observations may have reflected the fact that microbial biomass C, N, and P were all main but independent components, associated with their respective enzyme activities [40,95]. In addition, not all soil enzymes are exclusively derived from microorganisms.…”
Section: Correlations Between the Soil Attributes Testedmentioning
confidence: 99%